A SEMIOTIC ANALYSIS ON WHISKAS’S BIG CAT LITTLE CAT EDITION PRINTED ADVERTISEMENT - NISA, NABILAH KHOIRUN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotics, Whiskas, Big Cat Little Cat, printed advertisement. Advertisement can’t be separated with human life. It is a mass marketing technique which persuades the consumers to buy the product which is being advertised. The writer use Whiskas’s Big Cat Little Cat Edition printed advertisement to analyze. There are two problems of the study namely (1) What kinds of semiotic signs are used on Whiskas’s Big Cat Little Edition Printed Advertisement; (2) What is the meaning of each sign used on Whiskas’s Big Cat Little Edition Printed Advertisement.In this study, a qualitative approach by document analysis is applied  to analyze and identify the signs, find out the meaning of the sign and the relation between the slogan and the sign found in Whiskas’s Big Cat Little Cat Edition Printed Advertisement. The writer uses Peirce’s typology on sign in analyzing the dataBased on the result, the writer found that there are signs total by 69 signs consisting of 32 icons, 27 indexes and 10 symbols found in the advertisements based on Peirce’s typology of sign theory. Based on the study that has been conducted towards the printed advertisement of Whiskas’s, the iconic signs were mostly used. Each sign has the role to strengthen and support the idea of the advertisement. The logo of Whiskas and the slogan “feeding your cat’s insctinct” appears in almost all of the advertisement. They become the controller of the advertisement’s idea.The researcher suggests Faculty of Cultural Studies to provide more books about semiotic both in English and Bahasa Indonesia since there are only a few books available in the library. The next writers are also suggested to find out other research’s object such as billboard advertisement, TV advertisement, internetadvertisement, movie posters, political cartoons and so on to gain a better understanding in Semiotic.